Shifts in Contraceptive Use in the City of Tehran, Iran: 2000-2014 - Amir Erfani; Javad Shojaei (مراقبت پرستاری و مامایی ابن سینا, 2020)
Introduction: Current data on changes in contraceptive use is required to prevent unintended pregnancies. This study aims to study trends, and patterns of contraceptive use from 2000 to 2014. Methods: This survey research uses data from three fertility surveys conducted in 2000, 2009, and 2014 respectively among representative samples of 1396, 2,934 and 3012 married women aged 15-49 living in the capital city of Tehran. The prevalence of contraceptive methods was estimated according to women’s socio-economic and demographic characteristics. Results: In 2014, 82% of women used contraceptive methods (48% modern methods, and 34% traditional methods). Withdrawal (33%) and condoms (21%) had the highest prevalence, compared with female sterilization (9%), IUD (7%) and Pills (7%). Over 2000-2014, the use of withdrawal and condoms increased by 69% and 20%, respectively. In contrast, the prevalence of female sterilization, pills, male sterilization, and IUD decreased respectively by 20%, 42%, 45% and 51% over the same period. The use of withdrawal method increased with women’s age. Withdrawal and condom were used by 67% of contraceptive users, who mostly hold higher education levels, were employed, and lived in upper residential districts. In contrast, users of modern methods, namely sterilizations, IUD and pills, mostly hold lower levels of education and income, were unemployed, lived in the lower residential districts, and had two or more children. Conclusion: The increasing prevalence of withdrawal and condom signifies a need for provision of effective family planning education and counseling to prevent unintended pregnancy.